Study of the Genetic Diversity in Three Species Belonging to Family: Daphniidae (Crustaceae, Cladocera) Collected from different Regions in Baghdad Province /Iraq - Bdoor Satar Albhadly (Journal of Global Pharma Technology, 2019)
Molecular methods were used to study three species belonging to the family of water fleas Daphniidae (Crustaceae, Cladocera), one belongs to the genus Daphnia and two species belonging to the genus Simocephalus. Collected from different places in the Baghdad province / Iraq (Al-Adhamiya Cornish, Al-Shula neighborhood, Brahim Bin Ali area, Al-Zawra Park, Lake of games city). The results showed that there are two species: D. magna, S. vetulus, were registered in Iraq, while the species S.congener recorded in Iraq for the first time. The genes COI, 16s, that of mtDNA, and 18s of the nucleus studied for the purpose of obtaining genetic diversity among species and for detecting the differences in the studied genes. This included DNA extraction from a group of individuals resulting from an adult female reproduction that carries the same genetic features of the mother (Monoclonal) produced from Parthenogenesis to get Iso- female line. DNA sequencing analysis of the three species of the water flea family was carried out using the forward primers that used with the reverse primers in magnification of parts of the genes 18s, 16s and COI. It was observed that there were variations in the sequences of the nitrogen bases of both genes when comparing the study samples with Standard reference sequences from around the world, and recorded sequences of nitrogen bases for study samples at the NCBI site and there was a genetic diversity of the same species by different sampling sites in the form of substitutions in the sequences of the nitrogen bases of the studied samples of the COI and 18s genes, while for 16s gene, no differences were observed for the same species, The genetic relationships tree among the studied species was drawn and compared to standard samples from results of the same studies in other countries that registered in NCBI for each of the three genes and the study results showed that the maximum likelihood of changing in nucleotides among the three species was that there were genetic differences between Simocephalus and Daphnia ,while the two species of the Simocephalus were found to be common in the same branch, and there was a similarity between them, While there were no significant differences among the species.Keywords: Daphnia, Simocephalus, RFLP, mtDNA, COI.